Global, regional, and national burden of syphilis, 1990–2021 and predictions by Bayesian age-period-cohort analysis: a systematic analysis for the global burden of disease study 2021 - Yu, Wenxia; You, Xiaoyan; Luo, Wei (Frontiers in Medicine, 2024)
Objective To comprehensively assess the global burden of syphilis and related risk factors over 1990–2021, forecast future disease trends, and understand the impact of syphilis on global health. Methods Global Burden of Disease Study 2021 (GBD 2021) data were used for age-, sex-, and region-stratified analysis of the numbers and age-standardized rates (per 100,000 population) of syphilis incidence, prevalence, deaths, and disability-adjusted life years (DALYs). Next, a differential analysis of syphilis risk factors was performed. Finally, trends for years after 2021 were predicted using Bayesian age–period–cohort (BAPC) prediction models. Results In 2021, the total number of syphilis prevalence globally was 70,541,482.80 (95% uncertainty interval: 54,910,897.66–88,207,651.97), with the highest numbers noted in Central Sub-Saharan Africa [4,622.60 (95% uncertainty interval: 3,591.97–5,753.45)]. Over 1990–2021, the global age-standardized prevalence and incidence rates increased, whereas the age-standardized death and DALY rates decreased. Among all groups, infants aged <5 years demonstrated the highest age-standardized DALY rates. Moreover, the lower the sociodemographic index (SDI), the higher was the age-standardized rate. The primary factor contributing to syphilis disease burden was identified to be unsafe sex. BAPC analysis revealed an overall increase in age-standardized prevalence rate in the <5-year age group over 1990–2035, and the highest age-standardized prevalence rate occurred in the 25–34-year age group. Conclusion Between 1990 and 2021, syphilis occurrence and prevalence increased consistently. Projections indicated a continual increase in syphilis incidence in children aged <5 years, and age-standardized prevalence rates were the highest in adults aged 25–34 years. Our results regarding the epidemiological trends of syphilis and its variations across regions, age groups, and sexes may aid policymakers in addressing the global impact of the disease effectively.